MicroRNA-128-3p-mediated depletion of Drosha promotes lung cancer cell migration. (11th December 2017) - Frixa, Tania; Sacconi, Andrea; Cioce, Mario; Roscilli, Giuseppe; Ferrara, Fabiana Fosca; Aurisicchio, Luigi; Pulito, Claudio; Telera, Stefano; Carosi, Mariantonia; Muti, Paola; Strano, Sabrina; Donzelli, Sara; et al.
Abstract : We identified a microRNA, miR-128-3p, able to induce a widespread miRNAs down-regulation in NSCLC, impinging on the migratory ability of lung cancer cells. Abstract: Alteration in microRNAs (miRNAs) expression is a frequent finding in human cancers. In particular, widespread miRNAs down-regulation is a hallmark of malignant transformation. In the present report, we showed that the miR-128-3p, which is up-regulated in lung cancer tissues, has Drosha and Dicer, two key enzymes of miRNAs processing, as the main modulation targets leading to the widespread down-regulation of miRNA expression. We observed that the miRNAs downregulation induced by miR-128-3p contributed to the tumorigenic properties of lung cancer cells. In particular, miR-128-3p-mediated miRNAs down-regulation contributed to aberrant SNAIL and ZEB1 expression thereby promoting the epithelial-to-mesenchymal transition (EMT) program. Drosha also resulted to be implicated in the control of migratory phenotype as its expression counteracted miR-128-3p functional effects. Our study provides mechanistic insights into the function of miR-128-3p as a key regulator of the malignant phenotype of lung cancer cells. This also enforces the remarkable impact of Drosha and Dicer alteration in cancer, and in particular it highlights a role for Drosha in non-small-cell lung cancer cells migration.